(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
This article examines the interrelationship of the concepts of ecology and the "green" economy, "green" space, and "green" financing, which have become urgent problems of our time. In recent years, climate change, the ecological crisis, and the limitation of natural resources have posed new challenges to the global financial system. The concept of "green" financing is being formed as a way to solve these problems. Green financing is a set of financial strategies aimed at ensuring sustainable economic growth in an environmentally safe manner.